UPAYA BALAI BESAR KONSERVASI SUMBER DAYA ALAM RIAU DALAM PENANGGULANGAN TINDAK PIDANA ILLEGAL LOGGING DI KAWASAN SUAKA MARGASATWA BUKIT RIMBANG DAN BUKIT BALING - Haryanto, Popo; Erdianto, Erdianto; Elmayanti, Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Forests have a very important position and role in supporting national development. The Constitution of the Republic of Indonesia of 1945 Article 33 paragraph (3) explains that